The impact of different standing positions on gluteus medius activation and lumbar lordosis in LBP-developers during prolonged standing. - Saeedeh Abbasi; Hooman Minoonejad; Hamed Abbasi; Seyed Hamed Mousavi (PLoS ONE)
Low back pain (LBP) development has been associated with increased hip muscle co-activation and lumbar lordosis during standing in previously asymptomatic individuals. It is commonly advised to use footrests to relieve LBP. The impact of adjusting arm position on lumbar biomechanics can also be impressive. This study aimed to compare the effects of normalized footrest height and changing arm position on Gluteus medius (GMed) muscle activity, lumbar lordosis, and pain intensity. Twenty-four female pain developers (PDs) were recruited, identified by a > 10 mm increase on the visual analog scale (VAS) during prolonged standing. Electromyography (EMG) recorded GMed activity, and photogrammetry measured lumbar lordosis at time points over one hour-standing. The first group (A) used the footrest intermittently, while the second group (B) additionally changed their arm positions. These variables were analyzed using repeated measures (between/within) ANOVA. No significant interaction was observed between the groups in right and left GMed co-contraction index (CCI) (p =  0.14). However, both groups exhibited a significant decrease in CCI during prolonged standing (time *  condition: p =  0.003). Additionally, Group B consistently demonstrated lower overall levels of co-contraction across time (p =  0.01). An approximate 6-degree reduction in lumbar lordosis was observed after prolonged standing with both interventions (group A and group B; p =  0.008 and p =  0.01, respectively), although no significant differences in lumbar lordosis were detected between the groups. Lumbar discomfort increased over time; however, the interventions significantly alleviated this discomfort after the intervention time point. Notably, group B reported lower pain intensity compared to group A (p =  0.007). Applying these interventions in the workplace could be beneficial to reduce discomfort for individuals who stand for long periods of time. Further research is needed to optimize these strategies and assess long-term benefits.